Patients with type 1 diabetes and albuminuria have a reduced brain glycolytic capability that is correlated with brain atrophy - Vestergaard, Mark B.; Laursen, Jens Christian; Heinrich, Niels Søndergaard; Rossing, Peter; Hansen, Tine Willum; Larsson, Henrik B. W. (Frontiers in Neuroscience, 2023)
Introduction. Patients with type 1 diabetes (T1D) demonstrate brain alterations, including white matter lesions and cerebral atrophy. In this case-control study, we investigated if a reason for this atrophy could be because of diabetes-related complications affecting cerebrovascular or cerebral glycolytic functions. Cerebral physiological dysfunction can lead to energy deficiencies and, consequently, neurodegeneration. Methods. We examined 33 patients with T1D (18 females, mean age: 50.8 years (range: 26-72)) and 19 matched healthy controls (7 females, mean age: 45.0 years (range: 24-64)). 11 (33%) of the patients had albuminuria. Total brain volume, brain parenchymal fraction, grey matter volume and white matter volume were measured by anatomical MRI. Cerebral vascular and glycolytic functions were investigated by measuring global cerebral blood flow (CBF), cerebral metabolic rate of oxygen (CMRO2) and cerebral lactate concentration in response to the inhalation of hypoxic air (~12% fractional oxygen) using phase-contrast MRI and magnetic resonance spectroscopy (MRS) techniques. The inspiration of hypoxic air challenges both cerebrovascular and cerebral glycolytic physiology, and an impaired response will reveal a physiologic dysfunction. Results. Patients with T1D and albuminuria had lower total brain volume, brain parenchymal fraction, and grey matter volume than healthy controls and patients without albuminuria. The inhalation of hypoxic air increased CBF and lactate in all groups. Patients with albuminuria had a significantly (p=0.032) lower lactate response compared to healthy controls. The CBF response was lower in patients with albuminuria compared to healthy controls, however not significantly (p=0.21) different. CMRO2 was unaffected by the hypoxic challenge in all groups (p>0.16). A low lactate response was associated with brain atrophy, characterized by reduced total brain volume (p=0.003) and reduced grey matter volume (p=0.013). Discussion. We observed a reduced response of the lactate concentration as an indication of impaired glycolytic activity, which correlated with brain atrophy. Inadequacies in upregulating cerebral glycolytic activity, perhaps from reduced glucose transporters in the brain or hypoxia-inducible factor 1 pathway dysfunction, could be a complication in diabetes contributing to the development of neurodegeneration and declining brain health.